Essentials of managerial finance - Besley, Scott. (Thomson/South-western, 2008)
Trust the book that has already helped hundreds of thousands of students like you understand the importance of managerial finance theory and the practical impact these principles have on business today. This leading ESSENTIALS OF MANAGERIAL FINANCE, 14e offers a well-written, understandable, complete introduction that equips you with the basic financial management tools you need for business success. This edition's 18 chapters cover all the topics you need, including accounting statements, security markets, interest rates, taxes, risk analysis, time value of money, and the basics of security valuation. As practical as it is thorough, this edition's clear, concise, proven presentation style blends theory with a practical application of what you've learned. Actual industry examples show how financial principles operate within businesses throughout the world. This edition highlights topics of growing importance in business today, such as multinational finance and resolving ethical dilemma. An emphasis on Excel and the use of financial calculators prepares you to effectively use these important financial tools. Chapter openers, self-tests throughout each chapter, and useful chapter summaries ensure you understand and can connect financial management to today's business world. Thomson ONE: Business School Edition, packaged free with each new text, gives you access to the same research tools that finance professionals use everyday. You can further maximize your study time and efficiently complete assignments with this edition's innovative new CengageNOW online learning system that helps you focus on the areas of managerial finance you still need to master with multimedia tools and tutorials that prepare you for success.